2019
DOI: 10.1103/physrevphyseducres.15.010130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of secondary school quantum physics curricula of 15 different countries: Different perspectives on a challenging topic

Abstract: Secondary school level quantum physics (QP) courses have recently been implemented in the national curricula of many countries. QP gives opportunities to acquaint students with more recent physics and its applications and to discuss aspects of the nature of science. Research has shown that QP is a challenging area for students. Because the inclusion of QP in national curricula is rather new in most countries, it is interesting to compare QP curricula from these countries to make the choices by curriculum desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 81 publications
0
108
0
22
Order By: Relevance
“…Scientists use their creativity and imagination. In an international comparison of curricula, five NOS aspects were identified as particularly relevant for teaching and learning QP (Stadermann et al, 2019). Table 1 illustrates the connection between these NOS aspects and QP with some examples, and it summarises desired and undesired views of NOS for the understanding of QP.…”
Section: Creativity In Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Scientists use their creativity and imagination. In an international comparison of curricula, five NOS aspects were identified as particularly relevant for teaching and learning QP (Stadermann et al, 2019). Table 1 illustrates the connection between these NOS aspects and QP with some examples, and it summarises desired and undesired views of NOS for the understanding of QP.…”
Section: Creativity In Sciencementioning
confidence: 99%
“…To avoid spending much lesson time on administering the test and enabling fast data processing and feedback, we designed an online multiple-choice test. QP curriculum items in the Netherlands are similar to those in other countries (Stadermann et al, 2019). Our test covers seven main themes: light as wave (interference and diffraction), interaction between radiation and matter (energy absorption and emission in atoms), photoelectric effect, matter waves (de Broglie relationship, interference in the double-slit experiment), Heisenberg's uncertainty relation, the quantum model of atoms (particle in a box), and tunnelling.…”
Section: Design Of the Qp Concept Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we will focus only on school teaching experiences. QM has been only recently introduced at the high school level in Italy as well as in other countries' physics curricula [44]. However, at high school, several basic aspects of QM are targeted also in chemistry classes before being addressed in the physics course, even though the scope and formalism remain quite different.…”
Section: B Potential Sources Of Overconfidence In Qmmentioning
confidence: 99%
“…The study of quantum physics usually begins by analyzing the phenomena of emission and absorption of electromagnetic radiation. Actually, a recent analysis of secondary school quantum physics curricula of 15 different countries has shown that "discrete energy levels" and "interaction between light and matter" are two of the most commonly occurring items [6]. One of the introductory quantum physics goals is that students grasp a quantum model of emission and absorption of radiation in order to explain the emission and absorption spectra, in terms of both frequencies and spectral line intensities.…”
Section: Introductionmentioning
confidence: 99%